Students’ Saving Behaviour: Do Demographic Profile, Parents’ Background and Financial Literacy Matter? An Empirical Study in Private Universities in Selangor - Azlina Md Kassim, Aza; Tamsir, Fazilah; Azhar Zainal Azim, Zainal; Mohamed, Juliza; Nisa Meor Nordin, Hairin (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, most of the university students are already accumulating substantial debts from higher education fee loans, personal bank loans or overused of credit cards. The saving behavior among students is significantly important as they are easily exposed to be blacklisted borrowers. Therefore, this study examines the factors that influence students’ saving behavior. Six variables are included namely, education level, programmer, gender, race, family background and financial literacy. The study used a survey questionnaire to private universities in Selangor. In total, the study receives 235 returned questionnaires. The results of regression analysis indicate that education programme and sound financial literacy lead to positive saving behavior. Besides, parents who practices money saving are more likely to influence their children’s saving habit. However, the study finds that education level, gender and race have no relationship with saving behavior. The result indicates that it is important for parents to educate their children to save money as they are the role model of the family. Besides, educators and regulators may organize more finance management workshop to students and parents in order to enhance their knowledge on the importance of money saving.